1998
DOI: 10.1136/jmg.35.8.685
|View full text |Cite
|
Sign up to set email alerts
|

Distal 6p deletion syndrome: a report of a case with anterior chamber eye anomaly and review of published reports.

Abstract: We describe a 32 year old male with a distal 6p24.3->pter deletion. He has specific developmental anomalies of the anterior chamber ofthe eye and a cleft uvula which is consistent with the recent localisation of genes for iris development and orofacial clefting to distal 6p. In addition he has progressive sensorineural deafness and this may localise a gene for deafness to this region. We conclude that a refined distal 6p deletion syndrome exists and includes a characteristic facial appearance with hyperteloris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 12 publications
2
43
0
Order By: Relevance
“…The smallest deletion, estimated to 4.8 -6.7 Mb, could be detected with high-resolution chromosome analysis. That case, earlier reported by Law et al, 5 suggested a more specific distal 6p deletion phenotype, including characteristic facies with hypertelorism, a down-turned tented mouth, anterior chamber malformation of the eye, progressive sensineuronal deafness, cardiac defects and speech and motor delay. Our case with a 2.1 Mb distal deletion confirms this phenotype, and further narrows down the critical region for the genes involved.…”
Section: Discussionmentioning
confidence: 94%
“…The smallest deletion, estimated to 4.8 -6.7 Mb, could be detected with high-resolution chromosome analysis. That case, earlier reported by Law et al, 5 suggested a more specific distal 6p deletion phenotype, including characteristic facies with hypertelorism, a down-turned tented mouth, anterior chamber malformation of the eye, progressive sensineuronal deafness, cardiac defects and speech and motor delay. Our case with a 2.1 Mb distal deletion confirms this phenotype, and further narrows down the critical region for the genes involved.…”
Section: Discussionmentioning
confidence: 94%
“…Table II presents a summary of this patient in the context of previous reports of adults and adolescents with distal 6p deletions [Jalal et al, 1989;Palmer et al, 1991;Law et al, 1998;Davies et al, 1999b;Le Caignec et al, 2005]. The patient presented in this report has many typical features of 6p25 deletion syndrome, and appears to have greatest similarity to patient SG in Law et al, 1998 and patient 3 in Mirza et al, 2004, with respect to the phenotype and extent of deletion [Law et al, 1998;Mirza et al, 2004]. A normal karyotype in infancy, normal vision, few other health problems and lack of genetics followup likely contributed to lack of recognition of a diagnosable syndrome until she was specifically assessed as an adult.…”
Section: Discussionmentioning
confidence: 99%
“…The typical facial appearance consists of hypertelorism (present in 93%), downslanting palpebral fissures (69%), and midface hypoplasia with flat, broad nasal bridge (77%). 14,15,[27][28][29][30][31][32][34][35][36] In addition, a prominent forehead (present in 51%), micrognathia (21%) and tented mouth (48%) with various dental anomalies (44%) can be present. 11,[13][14][15][27][28][29][30][31][32][34][35][36] External ears are frequently low set (58%) and are often malformed (39%).…”
Section: Asdmentioning
confidence: 99%
“…14,15,[27][28][29][30][31][32][34][35][36] In addition, a prominent forehead (present in 51%), micrognathia (21%) and tented mouth (48%) with various dental anomalies (44%) can be present. 11,[13][14][15][27][28][29][30][31][32][34][35][36] External ears are frequently low set (58%) and are often malformed (39%). 14,15,[27][28][29][30][31][32][34][35][36] Microcephaly has been described in several cases.…”
Section: Asdmentioning
confidence: 99%
See 1 more Smart Citation